RETRACTED: Proxalutamide Reduces the Rate of Hospitalization for COVID-19 Male Outpatients: A Randomized Double-Blinded Placebo-Controlled Trial - McCoy, John; Goren, Andy; Cadegiani, Flávio Adsuara; Vaño-Galván, Sergio; Kovacevic, Maja; Situm, Mirna; Shapiro, Jerry; Sinclair, Rodney; Tosti, Antonella; Stanimirovic, Andrija; Fonseca, Daniel; Dorner, Edinete; et al. (Frontiers in Medicine, 2021)
Antiandrogens have demonstrated a protective effect for COVOD-19 patients in observational and interventional studies. The goal of this study was to determine if proxalutamide, an androgen receptor antagonist, could be an effective treatment for men with COVID-19 in an outpatient setting. A randomized, double-blinded, placebo-controlled clinical trial was conducted at two outpatient centers (Brasilia, Brazil). Patients were recruited from October 21 to December 24, 2020 (ClinicalTrials.gov number, NCT04446429). Male patients with confirmed COVID-19 but not requiring hospitalization (COVID-19 8-point ordinal scale <3) were administered proxalutamide 200 mg/day or placebo for up to 7 days. The primary endpoint was hospitalization rate at 30 days post-randomization. A total of 268 men were randomized in a 1:1 ratio. 134 patients receiving proxalutamide and 134 receiving placebo were included in the intention-to-treat analysis. The 30-day hospitalization rate was 2.2% in men taking proxalutamide compared to 26% in placebo, P<0.001. The 30-day hospitalization risk ratio was 0.09; 95% confidence interval (CI) 0.03 to 0.27. Patients in the proxalutamide arm more frequently reported gastrointestinal adverse events, however, no patient discontinued treatment. In placebo group, 6 patients were lost during follow-up, and 2 patients died from acute respiratory distress syndrome. Here we demonstrate the hospitalization rate in proxalutamide treated men was reduced by 91% compared to usual care.